2020
DOI: 10.1016/j.devcel.2020.02.019
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic Transcriptional Responses to Injury of Regenerative and Non-regenerative Cardiomyocytes Revealed by Single-Nucleus RNA Sequencing

Abstract: Highlights d Neonatal cardiomyocytes (CMs) in mice are heterogeneous d Immature CMs enriched in regenerative hearts enter the cell cycle upon injury d Defined transcriptome changes occur in regenerating CMs in response to injury d NFYa and NFE2L1 exert proliferative and protective functions, respectively, in CMs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(118 citation statements)
references
References 86 publications
10
108
0
Order By: Relevance
“…In this regard, SB203580‐mediated inhibition of p38α MAPK activity after cotreatment with PDBu or thrombin was insufficient to further increase the length of membrane protrusions or NNVM length in the absence of de novo nestin synthesis. Furthermore, consistent with the apparent disparate response among NNVMs observed in this study and previous studies from our laboratory, a similar paradigm was reported in neonatal mouse ventricular cardiomyocytes (Cui et al, 2020; Hertig et al, 2019, 2018; Meus et al, 2017). Employing single nucleus RNA sequencing, the study by Cui et al (2020) identified five distinct populations of neonatal mouse ventricular cardiomyocytes after the superimposition of a myocardial infarct on the neonatal mouse heart.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this regard, SB203580‐mediated inhibition of p38α MAPK activity after cotreatment with PDBu or thrombin was insufficient to further increase the length of membrane protrusions or NNVM length in the absence of de novo nestin synthesis. Furthermore, consistent with the apparent disparate response among NNVMs observed in this study and previous studies from our laboratory, a similar paradigm was reported in neonatal mouse ventricular cardiomyocytes (Cui et al, 2020; Hertig et al, 2019, 2018; Meus et al, 2017). Employing single nucleus RNA sequencing, the study by Cui et al (2020) identified five distinct populations of neonatal mouse ventricular cardiomyocytes after the superimposition of a myocardial infarct on the neonatal mouse heart.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, consistent with the apparent disparate response among NNVMs observed in this study and previous studies from our laboratory, a similar paradigm was reported in neonatal mouse ventricular cardiomyocytes (Cui et al, 2020; Hertig et al, 2019, 2018; Meus et al, 2017). Employing single nucleus RNA sequencing, the study by Cui et al (2020) identified five distinct populations of neonatal mouse ventricular cardiomyocytes after the superimposition of a myocardial infarct on the neonatal mouse heart. The neonatal mouse ventricular cardiomyocyte population designated Group 4 was highly enriched with embryonic genes and identified as the predominant population implicated in the cardiac regenerative response after myocardial infarction via their ability to re‐enter the cell cycle (Cui et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nuclei, on the other hand, are much more resistant to mechanical assaults and have been readily profiled using snRNA-seq in multiple systems (Grindberg et al, 2013;Habib et al, 2016Habib et al, , 2017Cui et al, 2020;Kebschull et al, 2020;Lau et al, 2020). snRNA-seq has many advantages including: 1) tissue can be kept in long-term storage at -80ºC prior to extraction (Wu et al, 2019;Ding et al, 2020); 2) snRNAseq reduces cell-type sampling bias (Denisenko et al, 2020); and 3) nuclei are more easily captured by microfluidics devices than large and/or fragile cells (Cui et al, 2020;Denisenko et al, 2020). Underscoring the utility of this protocol, high-quality nuclei can be isolated from frozen tissues which allows researchers studying low-abundance cell types to collect and freeze a large amount of tissue (over multiple days) to ensure that they have an adequate number of nuclei for downstream processing and analyses.…”
Section: Single-nucleus Rna-seq Can Be Used To Profile Cuticle-associmentioning
confidence: 99%
“…Although traditional literature suggests that cardiomyocytes proliferate early in gestation, and that postnatal cardiac growth is achieved exclusively through hypertrophy, recent evidence in humans demonstrates that cardiomyocytes continue to proliferate in the first year of life, and a small number remain proliferative for as long as 20 years [5]. Moreover in rodents, cardiomyocytes retain the ability to proliferate until the point of binucleation, which occurs on or before postnatal day 7 [6,7]. Work focused specifically on this developmental window has revealed that cardiomyocytes continue to undergo mitosis in an environment where the oxygen tension is low, even extending into adulthood, where whole animal hypoxiaexposure following myocardial infarction reduces cardiac damage and fibrosis by enhancing cardiomyocyte proliferation [5,8,9].…”
Section: Introductionmentioning
confidence: 99%